Effect of Palm Kernel Meal Inclusion on Growth Performance, Immune and Visceral Organ Weights and Cecal Lactic Acid Bacteria in Neonatal Broilers - Martínez , Yordan; León, Aroldo Botello; Gebeyew, Kefyalew (International Journal of Poultry Science, 2020)
Background and Objective: Feed represents up to 70% of the total cost of production in the poultry industry; the challenge is to find alternative sources available to increase economic profitability. The study aimed to evaluate growth performance, immune and visceral organ weights and cecal lactic acid bacteria in neonatal broilers fed 5, 10 and 15% of palm kernel meal in the diet. Materials and Methods: Overall, 1,152 birds of the Ross 308® genetic line were used, randomly distributed in four treatments and six repetitions per treatment during the first 10 days old. Isoproteic and isoenergetic diets were made. Results: The dietary inclusion with 5 and 10% palm kernel meal increased (p